Anthelmintic activity of silver-extract nanoparticles synthesized from the combination of silver nanoparticles and M. charantia fruit extract. Issue 1 (December 2016) - Rashid, Md.; Ferdous, Jannatul; Banik, Sujan; Islam, Md.; Uddin, A.H.M.; Robel, Fataha
Abstract Background Present study has been conducted to know the anthelmintic activity of polyaniline coated silver nanoparticles (AgNPs) synthesized fromMomordica charantia fruit extract. Methods By reduction of AgNO3 in presence of NaBH4, silver nanoparticles were prepared. After mixing silver nanoparticles and extracts, coating was given on nanoparticles using polyaniline. Prepared nanoparticles were characterized by Visual, UV, FTIR spectroscopy, SEM techniques, and TEM analysis. Results The FTIR results implied that AgNPs were successfully synthesized and capped with bio-compounds present in the extract. The result showed that death times of worm were 35.12 ± 0.5 and 59.3 ± 0.3 minutes forM. charantia extract and Ag-nanoparticles individually. But when these two combined together, paralysis and death time fall drastically which were only 6.16 ± 0.6 and 9.1 ± 0.4 minutes respectively. Albendazole tablet was used as standard, which made worms death in 3.66 ± 0.1 minutes. Conclusion Ag-Extract NPs showed strong anthelmintic activity against worm. This study has paved the way for further research to design new anthelmintic drug from the combination ofM. charantia and AgNPs.